The Repellent Effects of Some Plant Powders on Sitophilus Oryzae (L.) (Coleoptera: Curculionidae) on Stored Rice in Thi -Qar Province, Southern Iraq. - Nasser, Tahani Abduljabbar; Nasser, Ashjan Agar; Kadhim , Noor Abdulaala; Nahi, Waheeda Abed (University of Thi-Qar Journal of Science, 2024)
The study showed the repellent effect of three types of plant powders, Mentha, Myrtus and Ocimum basilica, against rice weevil Sitophilus oryzae (L.) (Coleoptera: Curculionidae), the results of the study showed that the Myrtus powder had the highest rate of repellent to insects. It reached the highest percentage of repellent outside the loop within 24 hours 41% at concentration of 6% where it was found that there was a significant difference in percentage compared to other plant powders (Mentha, Ocimum basilica) reached 39.5% and 37.5 %, respectively.